Potassium 6-Oxo-7,13,16,22-tetraazatetracyclo[12.6.2.18,12.017,21]tricosa-1(20),8(23),9,11,14,16,18,21-octaen-2-yne-15-carboxylate - Camille Blouet; Stéphanie Letast; Thomas Robert; Stéphane Bach; Noël Pinaud; Nicolas Joubert; Marie-Claude Viaud-Massuard; Jean Guillon; Cédric Logé; Caroline Denevault-Sabourin (Molbank, 2023)
Potassium 6-oxo-7,13,16,22-tetraazatetracyclo[12.6.2.18,12.017,21]tricosa-1(20),8(23),9,11,14,16,18,21-octaen-2-yne-15-carboxylate was synthesized through a multi-step pathway, starting from commercially available 3-iodo-1,2-phenylenediamine. Structure characterization of this new substituted macrocyclic quinoxaline compound was achieved using 1H NMR, 13C NMR, and HRMS spectral analysis. This new macrocyclic derivative demonstrated submicromolar potency on both Pim-1 and Pim-2 isoforms, with an interesting selectivity profile against a selected panel of human kinases.